The Hyper-Kamiokande experiment: Status and prospect - Umut Kose, on behalf of Hyper-Kamiokande collaboration (SciPost Physics Proceedings)
Hyper-Kamiokande is the next-generation neutrino observatory, aiming to tackle a broad spectrum of physics programs. These include probing leptonic CP violation through long baseline accelerator neutrino oscillations, determining neutrino mass ordering, potentially discovering the proton decay, and capturing neutrinos from supernova relics, other astrophysical sources, and the sun. As the world's largest underground Cherenkov detector, Hyper-Kamiokande boasts a fiducial volume eight times that of its predecessor, Super-Kamiokande. With 258 kton of ultrapure water as its medium, Hyper-Kamiokande is scheduled to begin its groundbreaking operations in 2027, located in Kamioka, Japan. This proceeding outlines the ambitious physics program of Hyper-Kamiokande, details of the design of the detector, and provides an update on its current status.